Step 1 :

Equation at the end of action 1 : (2x2 - 5x) - 3 = 0

Step 2 :

Trying to variable by dividing the center term2.1Factoring 2x2-5x-3 The very first term is, 2x2 the coefficient is 2.The center term is, -5x that is coefficient is -5.The last term, "the constant", is -3Step-1 : main point the coefficient of the very first term through the constant 2•-3=-6Step-2 : discover two factors of -6 whose sum equals the coefficient that the middle term, i m sorry is -5.

 -6 + 1 = -5 That"s it

Step-3 : Rewrite the polynomial dividing the center term making use of the two components found in step2above, -6 and also 12x2 - 6x+1x - 3Step-4 : add up the very first 2 terms, pulling out choose factors:2x•(x-3) include up the critical 2 terms, pulling out typical factors:1•(x-3) Step-5:Add increase the four terms of step4:(2x+1)•(x-3)Which is the desired factorization

Equation in ~ the end of step 2 :

(x - 3) • (2x + 1) = 0

Step 3 :

Theory - roots of a product :3.1 A product of number of terms amounts to zero.When a product of 2 or an ext terms amounts to zero, climate at the very least one that the terms must be zero.We shall now solve each term = 0 separatelyIn various other words, we room going to fix as plenty of equations together there are terms in the productAny systems of hatchet = 0 solves product = 0 together well.

Solving a single Variable Equation:3.2Solve:x-3 = 0Add 3 come both sides of the equation:x = 3

Solving a solitary Variable Equation:3.3Solve:2x+1 = 0Subtract 1 indigenous both sides of the equation:2x = -1 divide both political parties of the equation by 2:x = -1/2 = -0.500

Supplement : fixing Quadratic Equation Directly

Solving 2x2-5x-3 = 0 straight Earlier we factored this polynomial by separating the middle term. Permit us now solve the equation by perfect The Square and by using the Quadratic Formula

Parabola, recognize the Vertex:4.1Find the vertex ofy = 2x2-5x-3Parabolas have a highest or a lowest point called the Vertex.Our parabola opens up and accordingly has a lowest allude (AKA absolute minimum).We understand this even prior to plotting "y" because the coefficient of the an initial term,2, is optimistic (greater than zero).Each parabola has actually a vertical heat of symmetry that passes through its vertex. Thus symmetry, the heat of the contrary would, because that example, pass with the midpoint that the two x-intercepts (roots or solutions) the the parabola. The is, if the parabola has actually indeed two real solutions.Parabolas can model numerous real life situations, such as the height over ground, of an object thrown upward, ~ some duration of time. The peak of the parabola can carry out us with information, such together the maximum elevation that object, thrown upwards, have the right to reach. Therefore we desire to have the ability to find the works with of the vertex.For any kind of parabola,Ax2+Bx+C,the x-coordinate that the vertex is offered by -B/(2A). In our case the x coordinate is 1.2500Plugging right into the parabola formula 1.2500 because that x we can calculate the y-coordinate:y = 2.0 * 1.25 * 1.25 - 5.0 * 1.25 - 3.0 or y = -6.125

Parabola, Graphing Vertex and X-Intercepts :

Root plot for : y = 2x2-5x-3 Axis of the contrary (dashed) x= 1.25 Vertex at x,y = 1.25,-6.12 x-Intercepts (Roots) : root 1 at x,y = -0.50, 0.00 source 2 in ~ x,y = 3.00, 0.00

Solve Quadratic Equation by completing The Square

4.2Solving2x2-5x-3 = 0 by perfect The Square.Divide both sides of the equation by 2 to have actually 1 as the coefficient the the first term :x2-(5/2)x-(3/2) = 0Add 3/2 to both side of the equation : x2-(5/2)x = 3/2Now the clever bit: take it the coefficient the x, which is 5/2, division by two, offering 5/4, and also finally square it providing 25/16Add 25/16 to both political parties of the equation :On the best hand side us have:3/2+25/16The usual denominator that the two fractions is 16Adding (24/16)+(25/16) gives 49/16So including to both sides we finally get:x2-(5/2)x+(25/16) = 49/16Adding 25/16 has actually completed the left hand side right into a perfect square :x2-(5/2)x+(25/16)=(x-(5/4))•(x-(5/4))=(x-(5/4))2 points which space equal to the same thing are also equal to one another. Sincex2-(5/2)x+(25/16) = 49/16 andx2-(5/2)x+(25/16) = (x-(5/4))2 then, follow to the law of transitivity,(x-(5/4))2 = 49/16We"ll describe this Equation together Eq.

You are watching: How to factor 2x^2-5x-3

See more: Can You Put A 16G Earring In An 18G Hole Cartilage? Where Can I Buy An Ear Cuff

#4.2.1 The Square source Principle claims that when two things room equal, their square roots room equal.Note that the square root of(x-(5/4))2 is(x-(5/4))2/2=(x-(5/4))1=x-(5/4)Now, using the Square root Principle to Eq.#4.2.1 we get:x-(5/4)= √ 49/16 add 5/4 come both sides to obtain:x = 5/4 + √ 49/16 due to the fact that a square root has actually two values, one positive and also the other negativex2 - (5/2)x - (3/2) = 0has two solutions:x = 5/4 + √ 49/16 orx = 5/4 - √ 49/16 keep in mind that √ 49/16 can be created as√49 / √16which is 7 / 4